Penulisan Tugasan & Tesis - Anderson, Johnathan, author 652788; Poole, Milicent, author 652789; Marzita Puteh, translator 275894; Sadiah Baharom, translator 652790 (Kuala Lumpur : Institut Terjemahan Negara Malaysia, 2011)
Includes index.